De la recherche-création en traductologie à l’écriture créative : compte rendu d’un cheminement doctoral - Virginie BUHL (E-REA)
This paper draws upon a research-creation PhD thesis in translation studies which was based on a corpus comprising four novels destined to adult readers with child narrators and their translations into French. The analysis of the narrative and stylistic features of those novels led to an in-depth study of one of them – Room, by Emma Donoghue – and its translation. This reflection on my own work as a translator then led me to produce transcreations, experimental translations used as a tool for the reflective and creative analysis of the text material under study.The present contribution thus aims at outlining the reflection carried out in my PhD thesis and illustrate it with extracts from the creative translations that were fostered by my research. The narratological and stylistic analysis of the language of a five-year-old child narrator is complemented by textual experiments which serve as the basis of my reflection as a researcher and practitioner. These experimental transcreations are also an opportunity to think differently about the relations between the source text and its textual metamorphoses, about translation, intertextuality and writing.Using this experimental, creative approach to literary texts can also serve as the basis for bilingual creative writing workshops which could complement academic or professional translation classes.